STRATEGI KOMUNIKASI PEMASARAN MELALUI TIKTOK DALAM MENINGKATKAN KEPUTUSAN PEMBELIAN PADA PT CHERY ARTA KELAPA GADING - Muhammad Farhan Amiludin; Flora Meliana Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid growth of TikTok has shifted automotive marketing strategies from conventional approaches toward more personal and interactive digital marketing. PT Chery Arta Kelapa Gading utilizes TikTok as a marketing communication medium to increase consumer purchasing decisions amid competitive pressure in the automotive industry. This study aims to analyze the marketing communication strategy implemented TikTok using the AISAS Theory (Attention, Interest, Search, Action, Share) and Persuasive Communication Theory as its theoretical framework. This research applies a descriptive-analytical qualitative method within a constructivism-interpretivism paradigm. Data were collected through unstructured interviews, participant observation, and documentation involving five informants, then processed using the Miles and Huberman analysis technique consisting of data reduction, data display, and conclusion drawing. The findings show that the dealer successfully implemented the AISAS stages sequentially: leveraging TikTok's algorithm and trends to capture attention, educational content to build interest, interactive features to facilitate information search, an omnichannel strategy to drive purchase action, and consumer testimonials that trigger a sustainable marketing cycle. Elements of persuasive communication further reinforced message consistency and consumer trust. The study concludes that alignment between digital content and offline service is a key factor in the success of the marketing strategy.